If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = 3x + 4 Reorder the terms: 7 + 2x = 3x + 4 Reorder the terms: 7 + 2x = 4 + 3x Solving 7 + 2x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 2x + -3x = 4 + 3x + -3x Combine like terms: 2x + -3x = -1x 7 + -1x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -1x = 4 + 0 7 + -1x = 4 Add '-7' to each side of the equation. 7 + -7 + -1x = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 4 + -7 -1x = 4 + -7 Combine like terms: 4 + -7 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 23+4x= | | 52=2x+y | | 7+4x=2x-11 | | 4/5=x/50 | | (2a)/3=-4.54545454545 | | 0.14(y-9)+0.10y=0.4y-0.01(60) | | 10-(-10)-7-5= | | 2c=5c+-19 | | 2(n+9)=3n-5 | | -3(7-4)= | | -3(7-4)= | | 5x+19+74= | | 9-y^2=14x+3 | | 6(9x-8)=47 | | d-17=45 | | -38+3r=8(4r+7)-7 | | 4x-9=7+9x+19 | | -32=-3+7x+3(x-2) | | -5x+7+3x=-1 | | 2(x-3)=5(2x+4) | | b+5=5/11 | | -x-47=31-7x | | 1.2b-1.8=47.4 | | 2a/3+5=5/11 | | 10-(3y-3)=8-4y | | 6.8x-4.7=-17.62 | | -7+4x+4x=-7 | | 11(t-2)+3t=7(2t+5)-10 | | 4/3(8x-3)=16 | | 9-6n-(-5n)-(-8n)= | | 6n-15=4n+5 | | -24-a=78 |